The Nitrogen Removal Ability of Salt Marsh Improved After Grazing Prohibition - Li, Niu; Nie, Ming; Wu, Ming; Wu, Jihua (Frontiers in Marine Science, 2022)
Grazing prohibition has been used for some conservation purposes in salt marshes. However, the impact of this measure on microbe-mediated key nitrogen removal processes remains poorly understood. Therefore, this study assessed the impact of grazing prohibition on potential rates of nitrification and denitrification under short- and long-term grazing prohibition in high and middle elevation of the Dongtan salt marsh on Chongming Island, China. Compared with short-term grazing prohibition, we found that long-term grazing prohibition significantly increased nitrification and denitrification (except for nitrification in the high marsh), which indicates that the nitrogen removal ability of the salt marsh was improved along with the grazing prohibition time. Furthermore, we found that nitrification and denitrification in the high marsh were largely affected by NH4+ and soil moisture, respectively. Nitrification and denitrification in the middle marsh were mainly controlled by soil organic carbon (SOC) and nirS gene abundances, respectively. Our results indicate that the implementation of scientific and reasonable grazing prohibition policies in salt marshes has great potential to restore their ecosystem functions, maintain their ecosystem balance and realize their sustainable development.